Strategies for enhancing post-harvest quality and shelf life of tuber crops: Insights from physiological perspectives - Saravanan Raju (JOURNAL OF ROOT CROPS, 2023)
This comprehensive review explores various strategies aimed at improving the quality and extending the shelf life of tubers such as potato, cassava, sweet potato and yams after they are harvested. It focuses on the physiological aspects involved in post-harvest storage. The review delves into the changes that occur within the tuber crops during storage, such as metabolic and biochemical transformations, shifts in respiration rates and ethylene production, and modifications in the composition and texture of cell walls. Additionally, the review addresses common physiological disorders that can arise during the storage of tuber crops, discussing their causes and the impact of storage conditions on their development. The review further provides insights into pre-harvest considerations, optimized harvesting techniques, postharvest treatments for disease and pest control, and the optimization of storage conditions to maximize the shelf life of tuber crops. It emphasizes the significance of physiological markers and indicators in assessing tuber quality and their role in making informed decisions during the post-harvest phase. The review also explores advancements in post-harvest technologies, including modified atmosphere storage, cold storage, and innovative approaches for maintaining quality and inhibiting sprouting and discusses emerging trends in post-harvest physiology research, the challenges and opportunities for enhancing tuber crop quality, and potential areas for future investigation.